Ativação celular em pessoas saudáveis e pacientes infectados pelo HIV - Isadora Sofia Borges Saraiva (2015)
Aims: We performed this study in order to assess the activation of CD4+ and CD8+ T lymphocytes among persons with and without HIV infection, between 18 and 55 years of age. We also attempted to correlate degrees of activation with clinical variables and, among HIV positive patients, with response to antiretroviral therapy. Methods: We performed a cross-sectional study by sequentially including patients with HIV infection who are followed at Centro de Treinamento e Referência em Doenças Infecciosas e Parasitárias Orestes Diniz (CTR - DIP Orestes Diniz). As HIV negative controls, we included volunteers among the clinic and laboratory staff, with known HIV negative status. Cell activation was defined as percent of CD4+ and CD8+ T lymphocytes expressing CD38 and HLA-DR markers by means of immunophenotyping. Patient history and laboratory data were obtained from the patient's medical chart. Results: We studied a total of 69 subjects, 49 HIV positive patients and 20 HIV negative controls. There was increased activation of both CD4+ and CD8+ T lymphocytes among HIV positive patients, when compared with HIV negative volunteers. The subgroup of HIV positive patients with high viral loads showed increased cell activation when compared with either HIV positive patients on antiretroviral therapy with lower viral loads or non-progressing HIV positive patients. There was no significant difference in cell activation between the subgroup of HIV positive patients on antiretroviral therapy and lower viral loads and the subgroup of non-progressing HIV positive patients. Conclusions: We showed that markers of T lymphocyte activation were increased in HIV positive patients, when compared with HIV negative subjects. Also, among subgroups of HIV positive patients, T lymphocyte activation was increased among patients with higher viral loads. Nevertheless, there was no correlation of degree of activation with either viral load or lymphocyte count.